Nutritional, physicochemical stability, microbial survivability and sensorial evaluation of legume yogurts - Jamalullail, Nurul Aini; Chan, Yong Lin; Tang, Teck Kim; Tang, Chin Ping; Lai, Oi Ming (Slovak University of Agriculture, 2022)
Legumes and probiotics are versatile food ingredients that can be incorporated into nutritious food products. In this study, legume yogurts from legume flours (8 w/w) and legume milks (16 w/w) were formulated using soybean (Glycine max), pigeon pea (Cajanus cajan),and mung bean (Vigna radiata). The formulations were incorporated with sugar (7), xanthan gum (0.5), and commercial mix cultures containing starter cultures (Streptococcus thermophilusand Lactobacillus bulgaricus) and probiotics (L. acidophilus, L. Casei,and Bifidobacterium longum), followed by fermentation at 37°C until they reached pH 4.5. Legume yogurts were analyzed for their chemical compositions, amino acid content,and sensory evaluation. Changes in pH, titratable acidity, color, water holding capacity (WHC), rheological properties, and microbial survivability were also evaluated during storage at 4°C for 28 days. Total solid (≥11.63), moisture (≥81.44),and protein (1.62 to 5.12) contents were recorded, while glutamic acid, aspartic acid,and lysine werethe most prevalent amino acids detected in the legume yogurts. During storage, the pH significantly decreased (P>0.05) while the titratable acidity increased. The legume yogurts showed shear-thinning properties (n<1) with reduced WHC during storage. The lactic acid bacteria survivability remained ≥7 log cfu/ml until the end of storage, except for B. longum. Desirable consistency, sweetness,and sourness were obtained from the sensorial evaluation. However, there wasalso an unfamiliar taste that developed from the products which affected their overall acceptability. In conclusion, legumes are great lactic acid bacteria carrier and their utilization provide a promising alternative for dairy substitutes.